2017
DOI: 10.1002/agr.21530
|View full text |Cite
|
Sign up to set email alerts
|

Farmgate prices, retail prices, and supermarkets' pricing decisions: An integrated approach

Abstract: Agricultural and food prices exhibit several empirical regularities that are not easily explained by conventional perfect competition or market power models, including asymmetric price transmission, food price rigidity, farmgate price volatility, and low correlation between prices at different stages of the supply chain. We focus on this set of market features and conclude that they can be the outcome of a competition model where supermarket use promotions to strategically attract basket shoppers. We present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In line with other studies (e.g., Li et al, 2006; Russo & Goodhue, 2018), we find empirical inconsistencies in food prices which deviate from the expectations derived from perfect competition models. Recent developments, such as the increased power concentration of retailers (Hovhannisyan et al, 2018), led to an increased attention toward farmer–retail relations in agricultural supply chains (Sexton, 2013).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…In line with other studies (e.g., Li et al, 2006; Russo & Goodhue, 2018), we find empirical inconsistencies in food prices which deviate from the expectations derived from perfect competition models. Recent developments, such as the increased power concentration of retailers (Hovhannisyan et al, 2018), led to an increased attention toward farmer–retail relations in agricultural supply chains (Sexton, 2013).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…As we illustrate in the following sections, the competitive environment in the agricultural and food sectors has evolved in ways such that the traditional tools illustrated so far lose their predictive power . Research has identified several limitations to the classical market power framework in capturing new developments, specifically: organization of agrifood markets; inter alia quality and asymmetric information (e.g., Caswell & Mojduszka, ) due to the presence of experience (Nelson, , ) and credence attributes (Darby & Karni, ); retailer pricing strategies (e.g., Li, Sexton, & Xia, ; Russo & Goodhue, ); long‐run concerns (e.g., Crespi et al., ; Mérel & Sexton, ); and sunk costs and secure supply (e.g., Sexton, ).…”
Section: Traditional Methods To Asses Market Power In the Agrifood Sementioning
confidence: 99%
“…As consumers shop simultaneously for a basket of products, there is an inherent “complementarity in purchase” that characterizes their shopping. It is conceivable that as food retailers maximize profits over a large number of products and product categories, they take purchase complementarity into account when setting prices (see Russo & Goodhue, , in this special issue). Recently, this behavior has been studied in both the theoretical (e.g., Rhodes, ; Smith, & Thomassen, ) and applied literature.…”
Section: Product Differentiation: Asymmetric Information Collective mentioning
confidence: 99%
“…In line with other studies (e.g. Russo and Goodhue, 2018;Li et al, 2006), we find empirical inconsistencies in food prices which deviate from the expectations derived from perfect competition models. Recent developments, such as the increased power concentration of retailers (Hovhannisyan et al, 2018), led to an increased attention towards farmer-retail relations in agricultural supply chains (Sexton, 2013).…”
Section: Conclusion and Discussionsupporting
confidence: 87%